2022
DOI: 10.1186/s12883-022-02735-w
|View full text |Cite
|
Sign up to set email alerts
|

Acute percheron infarction: a precision learning

Abstract: Background So far, the diagnosis of acute artery of percheron (AOP) infarction is uncommon. In this study, patients with acute AOP infarction were studied to explore the relationship of imaging findings, clinical manifestations and prognosis of acute AOP infarction. Materials A total of 23 patients with acute AOP infarction in our institution from 2014 to 2019 were reviewed retrospectively. All cases were evaluated by computed tomography (CT) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…According to Zhang et al, patients with BPT and BPAT patterns of AOP infarctions demonstrated a good prognosis and meaningful recovery with appropriate treatment. However, this is not the case with the BPTRM counterpart [ 8 ], which was unfortunately present in our patient.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…According to Zhang et al, patients with BPT and BPAT patterns of AOP infarctions demonstrated a good prognosis and meaningful recovery with appropriate treatment. However, this is not the case with the BPTRM counterpart [ 8 ], which was unfortunately present in our patient.…”
Section: Discussioncontrasting
confidence: 62%
“…However, clinical presentations may vary due to the disparate functions of the implicated structures. Further described manifestations include vertical gaze palsy and ataxia (commonly seen with midbrain involvement), behavior and memory deficits (often associated with disruptions to the hippocampus or its connections), motor dysfunction, and speech difficulties [ 3 , 8 , 9 ]. It is noteworthy that in clinical practice, associating the symptoms with the underlying infarction/lesion poses a significant challenge to physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombolysis in AOP occlusion has been shown to be beneficial before. In a series of 23 patients presented by Zhang et al [19], 6 patients received thrombolysis and all of them had a good outcome at 90 days (mRS ≤ 2). However, none had additional involvement of the midbrain, as seen in our case 4.…”
Section: Discussionmentioning
confidence: 96%
“…There may be several reasons for the patient to have bilateral anterior thalamus infarction at the same time. Some literature reports that in a few patients, bilateral or unilateral thalamic nodular arteries are absent, and blood is supplied by the parathalamic median artery [7] . The fourth type of Percheron infarction is bilateral parathalamic median area combined with anterior thalamic infarction [8] .…”
Section: Discussionmentioning
confidence: 99%